Klinefelter's Syndrome with Maternal Uniparental Disomy X, Interstitial Xp22.31 Deletion, X-linked Ichthyosis, and Severe Central Nervous System Regression - Brault, Jennifer; Walsh, Laurence; Vance, Gail H.; Weaver, David D. (Journal of Pediatric Genetics, 2020)
We presented in this article a patient with Klinefelter syndrome (KS) (47,XXY) who had maternal nondisjunction and uniparental disomy of the X chromosome with regions of heterodisomy and isodisomy, an interstitial Xp22.31 deletion of both X chromosomes, and other problems. His mother also possesses the same Xp22.31 deletion. The patient presented with status epilepticus and stroke, followed by severe brain atrophy and developmental regression. His unusual clinical and cytogenetic findings apparently have not been reported with either KS or Xp22.31 deletions. Based on the patient's available genetic and biochemical information, we cannot satisfactorily explain his seizures, strokes, or catastrophic brain regression.
Keywords: Klinefelter syndrome; maternal nondisjunction; uniparental disomy; interstitial Xp22.3 deletion; X-linked ichthyosis; status epilepticus; stroke